Air Quality Analysis in Ternate Urban Area Based on Lichen Biological Indicators - Wa Inda; Rosita Tabaika; Lintal Muna (Golden Ratio of Social Science and Education, 2026)
Urban air quality is an increasingly important environmental issue due to increasing transportation activity and urban growth. This study aims to analyze air quality in the urban area of Ternate City using lichen as a biological indicator. The study was conducted at several locations representing main roads, residential areas, and areas with relatively good vegetation cover. The method used was a field survey with a purposive sampling technique, identification of lichen species, and calculation of the Shannon-Wiener Diversity Index (H’). The results showed that the lichen diversity index value in the main road area was low, while that in the residential and vegetated areas was medium. No high diversity index values were found at all observation locations, indicating that urban air quality in Ternate City is still under pressure due to anthropogenic activities, especially transportation. These findings confirm that lichens are effective as bioindicators of air quality and are relevant for application as a simple and sustainable environmental monitoring method in the archipelago.